2020
DOI: 10.1213/ane.0000000000005262
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Lower Preoperative Cognition With Intraoperative Electroencephalographic Features Consistent With Deep States of Anesthesia in Older Patients: An Observational Cohort Study

Abstract: BACKGROUND: Patients with low cognitive performance are thought to have a higher risk of postoperative neurocognitive disorders. Here we analyzed the relationship between preoperative cognition and anesthesia-induced brain dynamics. We hypothesized that patients with low cognitive performance would be more sensitive to anesthetics and would show differences in electroencephalogram (EEG) activity consistent with a brain anesthesia overdose. METHODS: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Thus, it is still unclear if altered cerebral perfusion is similar across delirium subtypes and if these neurophysiologic alterations resolve concurrently with delirium cessation. Furthermore, as excessive burst suppression has been previously associated with delirium, 61,62 as well as increased mortality in the ICU, 63 electroencephalography may be another viable non-invasive neuromonitoring device to provide additional neurological information as an adjunct to NIRS and/or TCD monitoring. Additionally, numerous studies did not report an a priori power analysis and had small sample sizes (n < 20), which may limit the validity of study findings.…”
mentioning
confidence: 99%
“…Thus, it is still unclear if altered cerebral perfusion is similar across delirium subtypes and if these neurophysiologic alterations resolve concurrently with delirium cessation. Furthermore, as excessive burst suppression has been previously associated with delirium, 61,62 as well as increased mortality in the ICU, 63 electroencephalography may be another viable non-invasive neuromonitoring device to provide additional neurological information as an adjunct to NIRS and/or TCD monitoring. Additionally, numerous studies did not report an a priori power analysis and had small sample sizes (n < 20), which may limit the validity of study findings.…”
mentioning
confidence: 99%
“…However, such a relationship between frontal alpha power and preoperative cognitive function was not observed in other EEG frequency bands. Gutiérrez et al [ 14 ] demonstrated that patients with lower MoCA scores exhibited lower alpha power and slower alpha peak frequency, which is consistent with the possibility that elderly patients with poor cognitive function receive an overdose of brain anesthesia compared to cognitively more robust patients. Similarly, Touchard et al [ 15 ] included 42 patients who had a preoperative cognitive assessment using MoCA with EEG information collected under a propofol-based general anesthesia, and they found that patients with cognitive decline had a lower alpha power and target TCI.…”
Section: Intraoperative Eeg Features and Pndmentioning
confidence: 65%
“…We hypothesized that the ability to more accurately identify and parameterize alpha oscillations would make it possible to characterize the relationship between alpha oscillations and cognitive health with greater statistical efficiency. To evaluate this idea, we fit a nested model to describe the presence of each patient's alpha oscillation and its frequency, if present, as a function of the patient's MoCA score in n = 35 subjects from the previously reported study described earlier [34]. We used a logistic regression model to represent the presence or absence of an alpha oscillation, in combination with a linear model to relate the alpha frequency to the MoCA score.…”
Section: Results: Eeg Under Anesthesiamentioning
confidence: 99%